EXPLORING SPATIAL AND TEMPORAL VARIATIONS OF AGRICULTURAL DROUGHT IN RORAYA WATERSHED USING NORMALIZED DIFFERENCE DROUGHT INDEX (NDDI) - Pramestika, Mutiara Indah (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2024)
Agricultural drought is a critical concern for food security, particularly in regions with significant climatic variability such as the Roraya Watershed in Southeast Sulawesi. This watershed is vulnerable due to its reliance on rain-fed agriculture and distinctive karst topography. This research aims to describe and map drought-prone areas within the Roraya Watershed using the Normalized Difference Drought Index (NDDI) from 2019 to 2023 comprehensively. The findings indicate a consistent presence of severe drought conditions across the watershed, which led to prolonged dry spells and decreased rainfall. Our results reveal that the Roraya Watershed’s agricultural areas are predominantly experiencing severe drought, with NDDI values ranging from 0.25 to 1. Despite some annual variations, the overall trend shows an increasing severity of drought conditions. This research highlights the necessity for targeted interventions and supports the development of effective drought mitigation strategies to enhance the resilience of agricultural systems in drought-prone regions. Keywords: Agricultural Drought, Roraya Watershed, Karst Topography, NDDI